2021
DOI: 10.3389/fpls.2021.671728
|View full text |Cite
|
Sign up to set email alerts
|

The Instability of Dimeric Fc-Fusions Expressed in Plants Can Be Solved by Monomeric Fc Technology

Abstract: The potential therapeutic value of many proteins is ultimately limited by their rapid in vivo clearance. One strategy to limit clearance by metabolism and excretion, and improving the stability of therapeutic proteins, is their fusion to the immunoglobulin fragment crystallizable region (Fc). The Fc region plays multiple roles in (i) dimerization for the formation of “Y”-shaped structure of Ig, (ii) Fc-mediated effector functions, (iii) extension of serum half-life, and (iv) a cost-effective purification tag. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
(131 reference statements)
1
8
1
Order By: Relevance
“…Importantly, using the glycoengineered ΔXTFT line (Strasser et al ., 2008) enabled the generation of IgG1 and IgM mAbs with a largely homogenous N-glycosylation profile, largely devoid of plant specific glycosylation. Nevertheless, some glycans at GS 1-3 of IgM are fucosylated, a feature also observed for other glycoproteins expressed in this RNAi line (Gattinger et al ., 2021). While each GS carried a highly reproducible single dominant N-glycan species, the pool of N-glycans in mammalian cell-produced mAbs is by far more heterogeneous, with substantial differences depending on the production conditions (Hennicke et al ., 2017; Hennicke et al ., 2019).…”
Section: Resultssupporting
confidence: 76%
“…Importantly, using the glycoengineered ΔXTFT line (Strasser et al ., 2008) enabled the generation of IgG1 and IgM mAbs with a largely homogenous N-glycosylation profile, largely devoid of plant specific glycosylation. Nevertheless, some glycans at GS 1-3 of IgM are fucosylated, a feature also observed for other glycoproteins expressed in this RNAi line (Gattinger et al ., 2021). While each GS carried a highly reproducible single dominant N-glycan species, the pool of N-glycans in mammalian cell-produced mAbs is by far more heterogeneous, with substantial differences depending on the production conditions (Hennicke et al ., 2017; Hennicke et al ., 2019).…”
Section: Resultssupporting
confidence: 76%
“…A recent study demonstrated the enhanced stability of recombinant human EPO-Fc transiently produced in N. benthamiana by the substitution of four residues crucial to the Fc dimerization interface. The resulting monomeric EPO was stably expressed, maintained its bioactivity, and became resistant to proteolytic degradation [179]. Based on their findings, the authors of this study suggested that the weak point the Fc fusion technology is the exposure of the vulnerable region due to the lack of CL and highlighted the importance of the disulfide bond bridges between the CH1 and CL for the stability of native IgG structure [179].…”
Section: Deactivation Of Proteasesmentioning
confidence: 95%
“…The most widely used fusion part of Fc in plant expression systems appears to be that of the human IgG1. It has been used in the production of a number of bioactive vaccines, including a dengue fever vaccine candidate derived from the consensus domain III (cEDIII) of dengue glycoprotein E [174,175], and therapeutic proteins, such as human EPO [176][177][178][179], human osteopontin (OPN) [180], and human angiotensin-converting enzyme 2 (ACE2), against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [181]. Fusion of human transferrin to the incretin hormone glucagon-like peptide-1 (GLP-1) has also led to robust accumulation of the protein and promising bioactivity in both transiently expressed and stable transgenic Nicotiana plants [114].…”
Section: Fusion Of Protein Partners/carriers/peptide Tagsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,15,16 Notably, conformational freedom is critical for efficient molecular function, especially for biomolecules with limited exibility and stringent function-associated orientations. [17][18][19][20] A typical example is native tetrameric (strept)avidin, which exists as a dimer-dimer, with each subunit contributing to the biotinbinding site of the neighboring monomer. [21][22][23] The biotinbinding site is approachable from one terminal end within the tetrameric architecture.…”
Section: Introductionmentioning
confidence: 99%